(3cTa GdEjgGe Yf hLg eSGFd TQGFY GdESdGes - (3GdeGRfOQGfj, eMeO Ydj Hf ebUhO Ydjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdQcf GdQGHY aj GdJhGHY ddUdhGJ cdgG GdhGLHI hGdefOhHI GdjhejI hZjQgG(B...s
(3BNQgG (B:s
(3GdSGHYI(B: (3EPG ONd hbJ fGadI(B... (3ZjQ UhQI GdeSCdI hdgPG CWdb GdLeGYI(B. (3hGdMeO ddg Ydi EJeGe(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis